PENGARUH DIMENSI KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN (Studi Kasus Pada Pengguna Jasa Penginapan Hotel Pandanaran Semarang) - Andria Ferry Rosmawan, 07.35.02.0724; Tjahjaningsih, Endang (Students Journal of Economic and Management, 2013)
One of [the] action to satisfy consumer by give service to consumer with as well possible. this fact can be seen, that there is several things that can give customer satisfactions that is customer total value yag consist of product value, service value, value personal, image value or image, and customer total cost that consist of monetary cost, time cost, energy cost, and idea cost (kotler, 2000: 50). with service quality existence either in in a company, will creat satisfaction to all the consumer. after consumer felts satisfied with product or service that accepted it, consumer will compare service that given. when does consumer felt genuinely satisfied, they will buy to repeat with give recommendation to another person to buy in place same. This watchfulness population entire entire hotel visitors pandanaran semarang. watchfulness sample election technique is done according to non probability sampling. steps that sample taking technique do distribution kuesioner by visit one who is spending at hotal pandanaran and ever spend the night at hotel pandanaran more than 1 time. to test researcher data quality does validity testing and reliabilitas. while to answer watchfulness hypothesis is used doubled regression analyzer, after previous done test normalitas data. besides, this watchfulness also test fit from model. test tool that with test f and determination coefficient. This watchfulness result shows that reliability, assurance, and emphaty positive influential and significant towards consumer satisfaction. While watchfulness result for another free variable, that is tangible, and responsive negative influential and significant towards consumer satisfaction. Key words: tangible, reliability, responsive assurance, emphaty, Â consumer satisfaction. Â